Nevirapine Increases Sodium/Iodide Symporter-Mediated Radioiodide Uptake by Activation of TSHR/cAMP/CREB/PAX8 Signaling Pathway in Dedifferentiated Thyroid Cancer - Shang, Hongxia; Zhao, Junyu; Yao, Jinming; Wang, Huanjun; Dong, Jianjun; Liao, Lin (Frontiers in Oncology, 2020)
Radioiodine therapy is a particularly important treatment for residual and metastatic thyroid cancer in post-operative patients with well-differentiated thyroid carcinoma (WDTC) for its satisfactory effect. However, around 30% WDTC may progress to dedifferentiated thyroid cancer (DeTC), which refractory to radioiodine treatment during treatment and then resulting in high recurrence and low survival rate. Nevirapine has been proved to be effective in inducing differentiation in several tumor cells and suppressing tumor growth. But, few studies pay attention to either its cytological effect on DeTC itself or the influence on effectiveness of radioiodine treatment. This study aims to investigate the therapeutic potential of nevirapine for DeTC and underlying mechanisms in this process. The results indicated that nevirapine inhibited dedifferentiated thyroid cancer cells (WRO 82-1 and dFTC-133) proliferation and increased the expression and translocation of sodium/iodide symporter (NIS). Furthermore, nevirapine simultaneously enhanced radioiodide uptake both in vitro and in vivo, and inhibited tumor growth in xenografts tumor. In addition, those therapeutic potentials of nevirapine were through TSHR/cAMP/CREB/PAX8 signaling pathway. This study demonstrates that nevirapine could be potentially used to improve radioiodine therapeutic efficacy in dedifferentiated thyroid cancer patients.